The influence of intrauterine growth retardation on cardiac function, left ventricular mass and superior vena cava return in newborns - Anindita Soetadji; Najib Advani; Asril Aminullah; Sudigdo Sastroasmoro (Indonesian Pediatric Society Publishing House, 2011)
Background Low birth weight (LBW) in neonates is a problem leading to high morbidity and mortality. Barker hypothesized that fetal cardiac remodeling during hypoxic conditions or maternal under􀁏nutrition is a risk factor for coronary heart disease in the young. Early vascular changes may influence cardiac function and newborns' cerebral blood flow. Objective The aim of this study was to detennine the effects of being small for gestational age (SGA) on newborns' cardiac function, left ventricular (LV) mass and superior vena cava (SYC) return. Methods This cross􀁏sectional study was conducted in Cipto Mangunkusumo Hospital from February to June 2008. LBW and nonnal newborns who fulfilled the inclusion criteria were recruited as subjects. Maternal history, infant physical examination, and echocardiography were obtained Mthin 48 hours oflife to exclude those with congenital heart disease, and assess cardiac function and SYC flow. Results Subjects were 21 preterm appropriate for gestational age (AGA), 19 SGA and 19 normal newborns. SGA newborns showed lower LV mass, stroke volume and cardiac output than normal newborns. However, these SGA parameters were not different from preterm AGA babies. In additio n, LV mass index was sig nificantly different but no difference ofSVC return between the three groups. Conclusion SGA newborns' LV function was lower than that of nonnal newborns, as low as pretenn AGA newborns. N onnal SVC return was observed in the three groups. This finding may be due to a brain􀁏sparing effect to maintain sufficient cerebral blood flow in the fetus.